Kajian Risiko Banjir Di Kabupaten Pati Berbasis Sistem Informasi Geografis - Muhammad Rofiq Andhesta; Sri Rahayu (Teknik PWK (Perencanaan Wilayah Kota), 2017)
Pati Regency is a city where almost every year, hit by the floods. Pati regency, whose land is mostly lowland regions have sunken to the flat topography is particularly vulnerable site affected by the flooding. Therefore, research by identifying the level of flood risk in Pati regency. In this study conducted with a quantitative approach, using the scoring method, overlay, weighting and descriptive analysis. Regional analysis of vulnerability to floods, flood vulnerability analysis region is determined by three variables: physical vulnerability, the vulnerability of social, economic vulnerability, the vulnerability of the environment.According to the results of processing and classification of risk maps using GIS (Geographic Information System) that in Pati District there are 181 village or sub-district 21 that indicated an impact of flooding. If you look at the results of the total area of the village affected by flooding risk in Pati District has a total area of 47.038 hectares with flooding risk classification level high up to very high.If seen in the results table which classified the risk that there are villages and districts that have to be followed-up for flood mitigation response efforts, villages and districts are District of Kayen, Kayen village with an area of very high risk classification and with an area of 1.221. 2million polygon risk 506 ha, Tegalombo Village, Dukuhseti Subdistrict with area high flood risk level classification 660.050 and with an area of polygons that affect the risk area of 1.012 ha.In the flood disaster risk assessment efforts in Pati District serves as the basis for developing a policy in this flood disaster management. This created a policy that would later become the basis for flood disaster management plans. In order government risk assessments that have been made are as a base, in making an action to be performed in the field in collaboration with stakeholders or the communities in disaster risk reduction.